IMPROVING READING AND WRITING SKILLS THROUGH SYNTHETIC STRUCTURE ANALYSIS (SAS) METHOD FOR STUDENTS OF CLASS 1 SD NEGERI 2 TAKIMPO, DISTRICT OF BUTON, SOUTHEAST SULAWESI - Harsinah Rafiudin; Sundari Hamid; Asdar Asdar (Publikasi dan UKI Press UKI Toraja., 2022)
Improving reading and writing beginning through the synthetic structure analysis method (SAS) as the focus of research departs from the reality in the field and the results of interviews with Indonesian teachers who are also grade 1 teacher at SD Negeri 2 Takimpo, generally in teaching reading and writing beginning using synthetic analysis structure methods but has not been implemented optimally, so students have not been able to read and write fluently. Based on this, this research is focused on learning to read and write beginning. The aim is to improve the reading and writing skills of the beginning students of class 1 SD Negeri 2 Takimpo by using the synthetic structure analysis method. The approach used in this research is a qualitative approach with an action research design. The research design was prepared using recycling cycle units including (1) planning, (2) implementation, (3) observation, (4) reflection. Reflection is carried out at the end of the cycle which is used as the design for the preparation of the next cycle planning. The stages of implementing the action are carried out collaboratively between researchers and practitioners. The form of learning to read and write beginning which is believed to be able to improve students' initial reading and writing skills is a form of learning that uses the implementation of the synthetic structure analysis method which consists of two parts, namely learning without using books and learning using books. The implementation is carried out in three stages, namely (1) the pre-reading and pre-writing stages, (2) the reading and writing stages, (3) the post-reading and post-writing stages. Based on process evaluation and evaluation of results in each lesson and based on success criteria, it was agreed in this study that it had been stated that (1) learning in the first cycle of action, both in terms of process and results had not been successful, there were still reading students who had not been able to pronounce letters perfectly, and in writing there are still deficiencies in letters in words, (2) learning in cycle II, both in terms of process and results have been successful, students are able to read and write sentences, (3) action learning in cycle III, both process and results have been successful, students are able to read and write using books.